(untitled) (Gilgameš, 2019)
The paper aims to provide a historical presentation and a brief description of the quite unknown manufacts kept in the Egyptian collection of the Archaeological Museum of the University of Pavia. The materials, most of them gifts given by scholars, travellers and scientists, in the fist mid of the 19th century, are a good evidence both of the so-called “Egyptomania” and the beginning of the interest in egyptologicals “studies” in Northern Italy. The reader will find, after a historical introduction, a short overview of the materials and a presentation of some ongoing projects for the valorization and the fruition of the collection itself.